Strategic Management of RahmaID in Improving Its Existence as an Online Media for Women and Islam - Amanati, Aisyi Ikrima; Hapsari, Twediana Budi (Universitas Muhammadiyah Yogyakarta, 2024)
The application of management has an essential role in increasing the existence of mass media. This study aims to determine the strategic management of online media as a digital communication channel through women's media based on Islamic principles. Along with the development of technology in Indonesia, online media is increasingly being used, leading to competition with one another, including in the women's segment. However, online media in the women and Islam segment still receives less attention, even though it has the same potential as other segments. For this reason, the study of strategic management in women's and Islamic online media has a role in creating an effective and efficient management system structure to achieve mass media goals. Theoretically, this study analyzes the pattern of implementing the Planning, Organizing, Actuating, and Controlling (POAC) management functions in online media. This study uses a descriptive qualitative approach to women's and Islamic online media to determine the management strategy used. Furthermore, this study identifies the factors that influence managing online media through POAC and provides an overview of the management strategies implemented to increase public existence. The results of this study contribute to the development of mass media for online media management, readers, and regulators.